An expanded maximum neural network algorithm for a channel assignment problem in cellular radio networks - Ikenaga, Katsuyoshi; Takenaka, Yoichi; Funabiki, Nobuo (Electronics & communications in Japan. Part 3, Fundamental electronic science, 2000)
In this paper, we propose a neural network algorithm that uses the expanded maximum neuron model to solve the channel assignment problem of cellular radio networks, which is an NP‐complete combinatorial optimization problem. The channel assignment problem demands minimizing the total interference between the assigned channels needed to satisfy all of the communication needs. The proposed expanded maximum neuron model selects multiple neurons in descending order from the neuron inputs in each neuron group. As a result, the constraints will always be satisfied for the channel assignment problem. To improve the accuracy of the solution, neuron fixing, which is a heuristic technique used in the binary neuron model, a hill‐climbing term, a shaking term, and an Omega function are introduced. The effectiveness of these additions to the expanded maximum neuron model algorithm is demonstrated. Simulations of benchmark problems demonstrate the superior performance of the proposed algorithm over conventional algorithms in finding the solution. © 2000 Scripta Technica, Electron Comm Jpn Pt 3, 83(11): 11–19, 2000